Evaluating a corporate strategy : a case study of Länsförsäkringar - Andersson, Helena; Jansson, Gustaf (SLU/Dept. of Economics, 2012)
The Swedish agricultural sector is currently undergoing a substantial structural change. The number of farm enterprises is continuously decreasing and the average farm size is increasing. In combination with increasing number of competitors in the insurance market, the competitive rivalry within this market has increased significantly. With this knowledge in mind, Länsförsäkringar Uppsala initiated this study, which aims to provide an understanding of customer’s view on customer value, related to agricultural insurance and financing. The intention is to investigate if Länsförsäkringar’s view on customer service corresponds with the customer’s view and whether there are any signs of strategic drift. The empirical data was collected in form of a case study. This was achieved by studying Länsförsäkringar’s strategic framework as well as performing three interviews within the company. Further, the customer’s view on customer value was collected in ten interviews carried out with current and former customers. The empirical data was then put in relation to theories and literature on strategy, resource-based theory on competitive advantage, and customer orientation. The results indicate that there are no immediate signs of strategic drift. The results also show that Länsförsäkringars strategy is well suited for the company’s characteristics and resources. However, even though the strategy corresponds well to the customer’s view on customer value, the empirical data indicate that the implementation of some parts of the strategy still needs attention. If more attention is not focused on these factors, there is an increasing risk of strategic drift in the future. The most important factors to focus on are; • Personal relation to the customers: One of the most important values for the customers is to have a personal relation to the company. To achieve this, it is of great importance that the customers are aware of who their contact person is. • Enhance synergies: It is of great importance to enhance the synergies between bank and insurance operations and to convince the customers that this is a service that is superior to the competitors’. The key factor to achieve this is to increase efficiency and collaboration in-house. • The local attachment: It is very important to communicate the benefits of Länsförsäkringars local attachment. It is also important to enhance these benefits. This can be achieved by mobilise the local representatives, and make them more active in the market. • High quality: Länsförsäkringar has chosen a differentiation strategy, that focus on high quality over low cost. In order to maintain credibility, it is of great importance to never fail in the delivery of this quality. Such a failure can in log run undermine the company’s reputation.